Human nature and social complexity: a common challenge for Chinese philosophy and marketing. (30th November 2009) - Paton, Michael; Henry, Paul
A review of the English language academic literature on East Asian business ethical practices reveals an inordinate focus on Confucian values. This paper argues that present day business value systems in East Asia are rooted in a much more complex array of philosophical stances including Legalism, Mohism, Daoism and Buddhism from a traditional perspective, and Christianity, Marxism and the will to power of Nietzsche as more contemporary influences. The paper then posits that the latter influences made great inroads into Chinese culture in particular because of the environmental history of China, and that such environmental influences have been much neglected in the conception of western business ethics. The paper concludes with discussion of the ubiquitous social embedding of marketing that faces the same human and social complexity explored by various East Asian scholars described in this paper. We note that modern marketers often fail to own up to their macro social responsibilities.